The future of communications in the 5G era - Harjono Padmono Putro (Sean Institute, 2024)
With much higher speed and capacity compared to previous generations, 5G technology is expected to provide a new paradigm in human interaction and communication between devices. This research aims to describe and analyze the impact and potential of communication transformation with the adoption of 5G network technology. This research uses a qualitative approach with descriptive methods. The results of this research reveal that the implementation of 5G technology has a significant impact on transforming the way we communicate and interact with the surrounding environment. Incredible internet speeds and better connectivity are opening up new opportunities in various sectors, such as healthcare, education and industry. Nonetheless, it was found that security and privacy challenges emerged as critical aspects that needed serious attention. Therefore, to ensure the successful implementation of 5G technology, collective efforts are needed in developing effective security solutions, so that the benefits of this technological revolution can be enjoyed without compromising data integrity and privacy.